The Arabs in history - Lewis, Bernard 1916- (Oxford paperbacks., 1993)
The author examines the key issues of Arab development - their identity, the national revival, and the social and economic pressures that destroyed the Arab kingdom and created the Islamic empire. He analyses the forces which contributed to the empire's decline, and the influence of the West.